English Foreign Language (EFL) Teachers’ Pedagogical Practices During Covid-19 Pandemic - Faisal Faisal; Sriati Usman; Abdul Kamaruddin; Aminah Suriaman (STABN RADEN WIJAYA WONOGIRI, 2022)
The objectives of this research were to identify the EFL teachers’ pedagogical practices in teaching English to the students and to find out the problems faced by EFL teachers in applying pedagogical practices to the students. This research was conducted through a qualitative approach. The data for this research were taken from 7 EFL Teachers in the Tinombo District. In collecting the data, the researcher used interview and document analysis instruments. Then, after analyzing the data obtained, it was concluded that the EFL teachers’ pedagogical practices in Tinombo district during pandemic covid 19 as a whole were using teaching methods and strategies that were tailored to the needs and abilities of students, giving various kinds of tests and assignments to students, understanding students' conditions, using media supporting the teaching process, assisting students in developing their potential and creativity, making good communication with students, conducting assessments and evaluations of learning materials, utilizing information on student learning outcomes, and using applications that support appropriate teaching strategies during a covid-19 pandemic. In addition, the main problems of teachers in applying Pedagogical Practices during the covid-19 Pandemic were the unstable internet network connection in that area and the concentration of students in learning decreases.